2015
DOI: 10.1071/sh14195
|View full text |Cite
|
Sign up to set email alerts
|

Neurosyphilis and the impact of HIV infection

Abstract: Abstract. Neurosyphilis is a complication of systemic syphilis. This review of the clinical presentation, diagnostic laboratory findings, treatment and management of neurosyphilis discusses the impact of HIV and the specific challenges it brings, focusing on areas of controversy, and highlighting important questions that remain to be answered.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
24
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(24 citation statements)
references
References 55 publications
0
24
0
Order By: Relevance
“…The clinical manifestations of neurosyphilis are similarly varied, and patients may remain asymptomatic for years. Levels of central neurological involvement can be classified into meningeal, vascular or parenchymatous forms with direct invasion of T. pallidum possible at each of these sites 9. Meningeal and vascular neurosyphilis are inflammatory processes that frequently coexist (meningovascular neurosyphilis), particularly in the early years of infection 10.…”
Section: Neurosyphilismentioning
confidence: 99%
See 2 more Smart Citations
“…The clinical manifestations of neurosyphilis are similarly varied, and patients may remain asymptomatic for years. Levels of central neurological involvement can be classified into meningeal, vascular or parenchymatous forms with direct invasion of T. pallidum possible at each of these sites 9. Meningeal and vascular neurosyphilis are inflammatory processes that frequently coexist (meningovascular neurosyphilis), particularly in the early years of infection 10.…”
Section: Neurosyphilismentioning
confidence: 99%
“…Meningeal and vascular neurosyphilis are inflammatory processes that frequently coexist (meningovascular neurosyphilis), particularly in the early years of infection 10. Meningeal involvement can present as aseptic meningitis with symptoms such as headache, photophobia and neck stiffness and can lead to complications such as cranial nerve palsies 9. Vascular syphilis can affect the arterial supply of the brain or spinal cord resulting in ischaemic stroke and, depending on the arterial territory involved, can cause different neurological deficits.…”
Section: Neurosyphilismentioning
confidence: 99%
See 1 more Smart Citation
“…Studies have also shown that syphilis has been associated with an increased risk of HIV transmission and acquisition [2,3]. Neurosyphilis may also develop earlier in the course of the disease in HIV-infected patients [4][5][6][7][8].…”
Section: Introductionmentioning
confidence: 99%
“…17,18 Ho and Spudich delve into the complex area of neurosyphilis and critically review its diagnosis and management in the context of HIV, including the thorny issue of when lumbar punctures are indicated. 19 Turning to the biology of T. pallidum, Ma et al detail the typing methods that have been used to characterise different strains and make a case for the development of more discriminatory genotyping methods. 20 These would potentially pave the way for typing that would have clinical utility such as information on the source of infection and predicting treatment response.…”
mentioning
confidence: 99%